Feminicidio y legislación Colombiana = Femicide and Colombian law - Zuluaga Muñoz, Deysy Alexandra (2009)
The concept of femicide in Latin America was developed by the ethnologist and anthropologist Marcela Lagarde, specifically for the case of women murdered in Ciudad Juarez (Mexico). The term has spread to other countries and in Colombia it was built into the reform to the Penal Code (Act 1257 of 2008) in this law is to protect women in such circumstances, this paper intends to make a sketch and a made known this as fact.